Still No Substantial Evidence to Use Prophylactic Antibiotic at Operative Vaginal Delivery: Systematic Review and Meta-Analysis - Yifru Berhan; Sisay Kirba; Achamyelesh Gebre (Obstetrics and Gynecology International)
Background. Postpartum maternal infection is still a common problem worldwide, mainly due to obstetric risk factors. The use of prophylactic antibiotic at operative vaginal delivery (OVD), taking it as a standalone risk factor, has been controversial. The purpose of this review was to rigorously evaluate the association of OVD with postpartum infection and shed light on such highly controversial issue. Methods. A computer-based literature search was done mainly in the databases of PUBMED, HINARI health research, and the Cochrane library. Systematic review and meta-analysis were done by including 14 articles published between 1990 and August 2019. Results. The average absolute risk of postpartum infection at OVD from seven large cohort studies was 1%. Few studies showed a weak association of OVD with postpartum infection without being adjusted to perineal wound, but the pooled meta-analysis showed statistically significant association with non-OVD. In the included randomized trial, 97% of the study participants had perineal wound for whom repairs were performed; the risks of maternal infection and perineal wound breakdown were comparable, and maternal infections other than perineal wound infection did not show significant difference between prophylactic antibiotic and placebo groups. The majority of included studies demonstrated a strong association of postpartum infection and perineal wound dehiscence with episiotomy and perineal tear. Conclusion. Both the relative and absolute risks of postpartum infection at OVD are extremely low unless accompanied by episiotomy and 3rd/4tht degree perineal tear. From previous studies, there is no substantial evidence to use prophylactic antibiotic at OVD, but episiotomy and perineal tear.